A Music Educator's Guide to Saving the Planet. (June 2019) - Shevock, Daniel J.; Bates, Vincent C.
As music educators, we always teach much more than the musical concepts and skills outlined in music curriculum standards. In this article, we discuss how music teachers can address what we believe is the most pressing issue of our time: environmental degradation. We first outline some specifics of ecological literacy in music education. This will include discussion of some songs that could form the center of a music curriculum for increasing ecological literacy. Next, we discuss cultivating ecological literacy using local musical practices and sounds of nature. Finally, we share an example of soundscape pedagogy aimed at increasing awareness of and propensities to care for the natural environment and ecological diversity. These components, singing, songwriting, and soundscape composition, are recommended as part of an overall creative pedagogical approach.